Resposta :
Explicação passo-a-passo:
[tex]\sf{ { - 2x}^{2} - 4x - 2 = 0 \: \: \: \: \: \: \div ( - 2)} \\ \\ \sf{ {x}^{2} + 2x + 1 = 0 } \\ \\ \sf{x = \frac{ - 2 \pm \sqrt{ {2}^{2} - 4 \times 1 \times 1 } }{2 \times 1} } \\ \\ \sf{x = \frac{ - 2 \pm \sqrt{ {2}^{2} - 4 \times 1} }{2 \times 1} } \\ \\ \sf{x = \frac{ - 2 \pm \sqrt{ {2}^{2} - 4 } }{2 \times 1} } \\ \\ \sf{x = \frac{ - 2 \pm \sqrt{ {2}^{2} - 4} }{2} } \\ \\ \sf{x = \frac{ - 2 \pm \sqrt{4 - 4} }{2} } \\ \\ \sf{x = \frac{ - 2 \pm \sqrt{0} }{?} } \\ \\ \sf{x = \frac{ - 2 \pm0 }{2} } \\ \\ \sf{x = \frac{ - 2}{2} } \\ \\ \boxed{\red{\mathsf{x = - 1}}}[/tex]
ATT:ARMANDO
- Para saber mais:
https://brainly.com.br/tarefa/38301491